Bio Chemical Study of Antithyroid Peroxidase Auto Antibodies , Magnesium and Cobalt in Hyperthyroidism Patients From Different Regions of Iraq. - AI Baiyati., N. k. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Sixty hyperthyroidism patients aged (20-45) years from different parts of Iraq , (20) from the North , (20) from Baghdad , (20) from the South of Iraq , and (20)control were tested for the presence of antithyroid peroxidase antibody(Tpo-Ab)and for Mg and Co levels in their sera. The results revealed a significant increase in (Tpo-Ab) in all patients group from the different parts of Iraq compared to control , also a significant increase in (Tpo-Ab) for the group from North compared to other parts. A significant decrease in Mg and Co levels in sera of patients from all parts of Iraq compared to control values , while no significant differences among patient groups were noticed ..In Conclusion anti - Tpo-Ab is specific for thyroid autoimmune disease , also Mg and Co were altered in response to thyroid hormones